The Effect of Lavender Aromatherapy to Improve the Sleep Quality of the Elderly at Tresna Werdha Abiyoso Social Service Center, Sleman - Melina Firda Andani; Widodo Arif (Yayasan Adra Karima Hubbi, 2023)
As part of aging or old age (elderly), general changes in circadian rhythms are referred to as earlier sleep phases. Prolonged sleep deprivation conditions can trigger many health system disorders, from a decrease in the body's immune system, weight gain due to uncontrolled appetite, and decreased level of concentration at work, to decreased patience and mood. One alternative non-pharmacological treatment to improve sleep quality is by providing lavender aromatherapy which will have a calming effect. This type of research is descriptive using a case study approach. A case study was conducted by applying non-pharmacological therapy with lavender aromatherapy to elderly respondents with sleep disorder nursing problems. The instruments used in this study were lavender aromatherapy, observation sheets, and sleep quality assessment sheets for the elderly. shows that there is an increase in the quality of sleep in the respondents. By doing this lavender aromatherapy therapy can help reduce sleep pattern disturbances in respondents. The results showed that there was an increase in sleep quality when patients could sleep soundly after being given lavender aromatherapy, so it can be concluded that there was an increase in sleep quality before and after giving lavender aromatherapy